Graphene: A Promising Two-Dimensional Support for Heterogeneous Catalysts - Fan, Xiaobin (Frontiers in Materials, 2015)
Graphene has many advantages that make it an attractive two-dimensional (2D) support for heterogeneous catalysts. It not only allows the high loading of targeted catalytic species, but also facilitates the mass transfer during the reaction processes. These advantages, along with its unique physical and chemical properties, endow graphene great potential as catalyst support in heterogeneous catalysis.